Data Driven Culture and Firm Performance: The Mediating Role of Customer Centric Innovation and Customer Loyalty - Wasiq, Mohammad (International Review of Management and Marketing, 2025)
The mechanism through which data driven culture enhances customer loyalty and firm performance has been unexplored and limited. In light of this research gap, this study examines the mechanism through which data driven culture enhances customer loyalty and firm performance by shedding light on the role of customer centric innovation. Therefore, the main aim of this study is to explore the mechanism of developing customer loyalty and firm performance based on data driven culture and customer centric innovation. With the help of resource-based view and dynamic capability theory, a conceptual model has been developed and validated with 389 responses from the owners of the SMEs. The study highlighted that data driven culture has a significant effect on customer centric innovation, customer loyalty and firm performance. Customer centric innovation had a positive effect on the customer loyalty and firm performance. Customer centric innovation has a mediating effect on the relationship between data driven culture and firm performance. Furthermore, Customer loyalty had a significant effect on the firm performance. In addition, customer loyalty had a mediating effect on the relationship between data driven culture and firm performance.